Targeting either GH or IGF-I during somatostatin analogue treatment in patients with acromegaly: a randomized multicentre study. Issue 1 (January 2018) - Dal, Jakob; Klose, Marianne; Heck, Ansgar; Andersen, Marianne; Kistorp, Caroline; Nielsen, Eigil H; Bollerslev, Jens; Feldt-Rasmussen, Ulla; Jørgensen, Jens O L
Abstract : Context: Discordant GH and IGF-I values are frequent in acromegaly. The clinical significance and its dependence on treatment modality and of glucose-suppressed GH (GHnadir ) measurements remain uncertain. Objective: To evaluate the effects of targeting either IGF-I or GH during somatostatin analogue (SA) treatment. Patients and Methods: 84 patients with controlled acromegaly after surgery ( n  = 23) or SA ( n  = 61) underwent a GH profile including an OGTT, at baseline and after 12 months. SA patients were randomized to monitoring according to either IGF-I ( n  = 33) or GHnadir ( n  = 28). SA dose escalation was allowed at baseline and 6 months. Main outcome measures: GHnadir and IGF-I at baseline and 12 months, and disease-specific Quality of Life (QoL). Results: IGF-I and fasting GH levels were comparable between the surgery and the SA group, whereas GHnadir (µg/L) was lower in the surgery group (GHnadir 0.7 ± 0.1 vs 0.3 ± 0.1, P  < 0.01). SA dose increase was performed in 20 patients in the GH group and in 8 patients in the IGF-I group ( P  = 0.02), which increased the number of concordantly controlled patients ( P  = 0.01). QoL was only mildly affected at baseline in all groups and did not changed consistently during the study. Conclusion: (1) Discordant values in terms of high GH levels are prevalent in SA patients and more so if applying glucose-suppressed GHnadir ; (2) targeting discordant levels of either GH or IGF-I translates into SA dose increase and improved biochemical control; (3) even though QoL was not improved in this study, we suggest biochemical assessment of disease activity to include glucose-suppressed GHnadir also in SA patients.